Successful use of dalbavancin in the treatment of gram positive blood stream infections: a case series - Connor Evins; Harrison Lancaster; Amanda E. Schnee (BMC, 2022)
Abstract Background Dalbavancin is a semisynthetic antibiotic used as an alternative to vancomycin for skin infections and osteomyelitis. Its long half-life decreases length of hospitalizations. This study analyzes the effectiveness of Dalbavancin for bacteremia and infective endocarditis. Methods The authors performed a retrospective chart analysis on patients who received Dalbavancin due to being poor candidates for PICC placement, poor candidates for prolonged hospitalization, or who were leaving against medical advice. Their hospitalizations were analyzed and results were compiled using descriptive statistics. Results Our cohort had 22 patients treated with Dalbavancin for bacteremia and 1 for endocarditis. They were treated with IV antibiotics, typically a regimen of at least vancomycin and a cephalosporin, for a median of 6.5 days prior to receiving Dalbavancin. 20 received one dose, while three received two doses. 22 had confirmed culture clearance and one denied repeat culture. There were no reported side effects from the medication, no readmissions for worsened infection, and no deaths from the infection. 15 patients had follow-up visits within 90 days. Conclusions Overall, patients responded well. The lack of readmission to the hospital indicates possible outpatient treatment. This would help decrease cost and comorbidities of long-term hospital stays. These positive results are limited by small sample size and treatment of other antibiotics prior to receiving Dalbavancin. Further research is required to accurately estimate the efficacy of Dalbavancin on bloodstream infections and endocarditis, but these results are promising especially for patients who are not candidates for long term hospitalization or outpatient IV access.